APLIKASI BUILDING MANAGEMENT - Sukarya, Robby Rohman; Yuliana, Ade; Taryana, Yudi; Samuel, Hizkia; Turnip, Ferlin Firdaus (Sinkron : jurnal dan penelitian teknik informatika, 2022)
One of the facilities and assets owned by Bank Indonesia is an official residence intended for permanent employees, office buildings, and other facilities such as borrowing rooms and goods that can be used by employees to support office activities. But in the implementation of maintenance of official houses and office buildings as well as the process of requesting room loan and goods still done manually. Therefore, a Building Management application is needed that can help the maintenance activities of official house buildings and office buildings as well as the process of requesting the loan of rooms and goods. Building Management application is a software that is used for building maintenance and management of all building needs including borrowing space and goods in an office building. This study aims to accelerate the process of requesting repairs to official office buildings and office buildings as well as borrowing rooms and goods. In addition, this application also generates automatic report recording output. The method in this study use V-Model is an extension of the waterfall model and is based on the association of the testing phase to each appropriate development phase. The result in this study is application to be built is based on the website using the CodeIgniter framework and the V Models system development method with stages arranged starting from verification which contains the needs analysis stage, design to the coding phase and also the validation process that contains testing of the application to determine application functionality and also know the level application usability for the user.